Rewarding Effects of Nicotine Self-administration Increase Over Time in Male and Female Rats. Issue 12 (14th April 2021) - Chellian, Ranjithkumar; Behnood-Rod, Azin; Wilson, Ryann; Bruijnzeel, Adriaan W
Abstract: Introduction: Smoking and the use of other nicotine-containing products is rewarding in humans. The self-administration of nicotine is also rewarding in male rats. However, it is unknown if there are sex differences in the reward-enhancing effects of nicotine self-administration and if the rewarding effects of nicotine change over time. Methods: Rats were prepared with catheters and intracranial self-stimulation (ICSS) electrodes to investigate the effects of nicotine and saline self-administration on reward function. A decrease in thresholds in the ICSS procedure reflects an enhancement of reward function. The ICSS parameters were determined before and after the self-administration sessions from days 1 to 10, and after the self-administration sessions from days 11 to 15. Results: During the first 10 days, there was no sex difference in nicotine intake, but during the last 5 days, the females took more nicotine than the males. During the first 10 days, nicotine self-administration did not lower the brain reward thresholds but decreased the response latencies. During the last 5 days, nicotine lowered the reward thresholds and decreased the response latencies. An analysis with the 5-day averages (days 1–5, 6–10, and 11–15) showed that the reward enhancing and stimulatory effects of nicotine increased over time. There were no sex differences in the reward-enhancing and stimulatory effects of nicotine. The nicotinic receptor antagonist mecamylamine diminished the reward-enhancing and stimulatory effects of nicotine. Conclusion: These findings indicate that the rewarding effects of nicotine self-administration increase over time, and there are no sex differences in the reward-enhancing effects of nicotine self-administration in rats. Implications: This study investigated the rewarding effect of nicotine and saline self-administration in male and female rats. The self-administration of nicotine, but not saline, enhanced brain reward function and had stimulatory effects. The rewarding effects of nicotine increased over time in the males and the females. Despite that the females had a higher level of nicotine intake than the males, the reward-enhancing effects of nicotine self-administration were the same. These findings suggest that in new tobacco and e-cigarette users, nicotine's rewarding effects might increase quickly, and a higher level of nicotine use in females might not translate into greater rewarding effects.